(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Languages spoken by the agglomerating ethnic groups in Nigeria instanced monopolistic closures. These closures were political, linguistic, socio-religious and settlement patterns. Regarding settlement patterns, Nigerians from particular ethnic groups tended to aggregate to live in defined patches of urban centres. For instance, are the Hausa quarters (Ama Awusa) or the Gariki in Igboland; Sabon Gari (where peoples from Eastern Nigeria or, particularly, the Igbo lived in Kano) in Northern Nigeria; the Munchi (from Tivland or the Tiv) in the Middle Belt of Nigeria; the Omumini ajaokuta (those who could eat stone without drinking water, referring to the Igbo) in Yorubaland; and Ndi ofe manu, referring to the Yoruba by the Igbo. There were equally day-to-day spoken monopolistic closures, such as “I bi Warri pikin” (I am a Warri youth) and “Ima kwa ndi anyi bu” (Do you know who we are by Igbo youths). Individuals and groups used their spoken languages to create barriers and monopolistic closures through voiced innuendoes against perceived, real or imagined marginalization, which became rife when the majoritarian and minoritarian concepts were blown out of proportion by Nigeria’s political elite. A worst-case closure manifested after the Biafra-Nigeria Civil War, when the Igbo, a hitherto majority group in the then Nigerian tripod of the Igbo, Huasa/Fulani and Yoruba majoritarian(s) umbrella became drowned into a minority through a gang-up of all the minority groups in the South-south and the South-south east. Ever since, the Igbo cried out to be marginalized. The paper concluded that the events in the political and socio-economic landscape of Nigeria were ethnically and politically motivated; and clinically underpinned by languages and their speakers. The paper was written with primary sources while secondary sources served subsidiary and complementary purposes.